Salvianolic Acid Alleviated Blood–Brain Barrier Permeability in Spontaneously Hypertensive Rats by Inhibiting Apoptosis in Pericytes via P53 and the Ras/Raf/MEK/ERK Pathway - Wu Q; Yuan X; Li B; Han R; Zhang H; Xiu R (Dove Medical Press, 2020)
Qingbin Wu,1,* Xiaochen Yuan,1,* Bingwei Li,1,* Ruiqin Han,2 Honggang Zhang,1 Ruijuan Xiu1 1Institute of Microcirculation, Chinese Academy Medical Sciences & Pecking Union Medical College; 2Institute of Basic Medical Sciences, Chinese Academy of Medical Sciences, School of Basic Medicine Peking Union Medical College, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaochen Yuan; Honggang ZhangInstitute of Microcirculation, Chinese Academy Medical Sciences & Pecking Union Medical College, 5, Dong Dan San Tiao, Beijing 100005, People’s Republic of ChinaTel +0086-10-65126407Fax +0086-10-65251957Email yuanxc@imc.pumc.edu.cn; zhanghg1966126@163.comObjective: To investigate the effect of salvianolic acid A (SA) on the permeability of blood–brain barrier (BBB) and brain microvascular pericyte apoptosis in spontaneously hypertensive rats (SHR).Methods: Evans Blue was used to determine the BBB permeability in control rats and SHR. Western blotting was used to evaluate the expression levels of relevant proteins in the pericytes isolated from the differentially treated animals. An in vitro model of hypertension was established by stimulating pericytes with angiopoietin-2 (Ang2). MTT assay was used to assess cell viability, and apoptosis and cell cycle distribution were analyzed by flow cytometry.Results: SA attenuated BBB permeability in SHR in a dose-dependent manner. It downregulated pro-apoptotic proteins including p53, p21, Fas, FasL, cleaved-caspase 3/caspase 3 and Bax in the pericytes of SHR and upregulated CDK6, cyclin D1, CDK2, cyclin E and Bcl2. In addition, SA activated the Ras/Raf/MEK/ERK pathway in a dose-dependent manner by increasing the levels of Ras, Raf, p-MEK1, p-MEK2, p-ERK1 and p-ERK2. Finally, SA reduced Ang2-induced apoptosis of cerebral microvessels pericytes and decreased the proportion of cells in the G0/G1 phase of the cell cycle by inhibiting the p53 pathway and activating the Ras/Raf/MEK/ERK pathway.Conclusion: SA reduced BBB permeability in spontaneously hypertensive rats, possibly by inhibiting Ang2-induced apoptosis of pericytes by activating the Ras/Raf/MEK/ERK pathway.Keywords: salvianolic acid A, blood–brain barrier, hypertension, pericytes, apoptosis